Enhancing Self-care Practices at Home for Epileptic Patients at Middle Euphrates Neuroscience Center in AL-Najaf City - Sahar Adham Ali; Hayder Ibrahim Ali (Kufa Journal for Nursing Sciences)
Background: Self-care Practices is a human regulatory functions that is a deliberate action to supply or ensure the supply of necessary materials needed for continued life, growth, development and to maintain of human integrity.